Pengaruh Model Pembelajaran Example Non Example berbantuan Poster Comment Terhadap Pemahaman Konsep Matematis - Doni Sabroni; Budi Koestoro; Asmiati Asmiati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2018)
This research has a purpose to know whether there is influence of the use of learning model Example Non Example assisted Poster Comment to the comprehension ability of mathematical concept. This research type is keyexperimental design, this research population is all students of class VII Madrasah Tsanawiyah (MTs) Al-Hidayah Srikuncoro academic year 2016/2017. In this research, the data analysis used is by using variance analysis (anova) one cell road is not same. The result of this research is that there is influence of learning model of Example Non Example with Poster Comment with the ability of understanding mathematical concepts, which the application of learning model Example Non Example with Poster Comment gives better concept of mathematics concept compared with the application of conventional model supported by Poster Comment and also the application of learning model Example Non Example with Poster Comment provides better mathematical concept capability compared to conventional learning model, and conventional teaching model application provides mathematical concept capability similar to conventional modeled learning application with poster comment.